Personal perception and body awareness of dysmenorrhea and the effects of rhythmical massage therapy and heart rate variability biofeedback—A qualitative study in the context of a randomized controlled trail. (August 2019) - Berger, B.; Böning, A.; Martin, H.; Fazeli, A.; Martin, D.D.; Vagedes, J.
Highlights: Dysmenorrhea ranges from body perception misbalances to overwhelming pain attacks hindering normal life. Drawing body silhouette diagrams, qualitative interviews and individualized practice help access embodied complaints. Rhythmical massage and heart rate variability biofeedback can both support stronger self-awareness. Perceived effects range from relaxing to clear benefits on the physical, emotional, social and cognitive level. Effects may be influenced by readiness to resonate with the therapeutic process. Abstract: Objective: The purpose was to involve women's personal experiences of daily life with primary dysmenorrhea (PD) and their body perceptions of the dysmenorrhea-related symptoms in relation to the treatment procedure and to explore the perception of Heart Rate Variability Biofeedback (HRV-BF) or Rhythmical Massage (RM) according to Ita Wegman as a therapeutic intervention within the framework of Anthroposophic Medicine (AM). Design: From 60 women who participated in our randomized controlled trial analyzing the effects of HRV-BF or RM, we examined 14 women to get an in-depth understanding of this prevalent disease, using a qualitative design. The women drew their body image before and after the 3-month-intervention on body silhouette diagrams and described their body-perceptions. Semi-structured interviews were conducted and analyzed using content analysis. Results: Women perceive dysmenorrhea as a disturbance of their daily lives. The body images showed the variations of experience, from misbalances of body perception to overwhelming attacks of pain hindering a normal life for several days per month. Perception of therapeutic interventions range from relaxing without effects on complaints to important changes and benefits on the physical, emotional, and/or social level. Both therapies can support stronger self-awareness through enabling a more differentiated sense of body-awareness, sometimes resulting in women experiencing fewer limitations in their daily lives. Effects may be influenced by the readiness to resonate with the therapeutic process. Qualitative interviews and body images can serve as tools to integrate individuality and help to integrate embodied more or less conscious aspects of complaints. Conclusions: The body silhouette diagram could be used systematically to include reflections of embodiment in the therapeutic and research settings and help to diagnose in advance the ability of participants to resonate with interventions. RM and HRV-BF influence self-awareness and may enable salutogenic and self-management capacities. For more effective treatment it may be helpful to make treatment suggestions based on an integrative individual history that includes preferences, expectations and a body silhouette diagram.